IL-18 provided in dying bacterial-infected macrophages induces IFN-γ production in functional T-cell hybridoma B6HO3 through cell conjugates. Issue 2 (February 2014) - Kubota, Koichi; Kadoya, Yuichi
We have previously reported that the co-culture of functional T-cell hybridoma B6HO3 with dying J774 macrophage cells infected with Listeria monocytogenes (LM) results in the production of IFN-γ by B6HO3 cells. Here, we explore the mechanism underlying this phenomenon. We found that IFN-γ production was dependent on IL-18, but that the dying LM-infected macrophages produced no more than 100 pg/ml of IL-18, much less than the amount of IL-18 required for stimulating B6HO3 cells to produce IFN-γ. Furthermore, IL-18 binding protein added to the co-culture was unable to easily gain access to IL-18 for neutralisation. B6HO3 cells formed cell conjugates with J774 macrophages, and IFN-γ-producing B6HO3 cells were spatially and temporally associated with LM-infected macrophage cell death that exhibited neither pyroptosis nor pyronecrosis. These results suggest that the IL-18 produced by dying LM-infected macrophages is released to the interface of the cell conjugates, thereby inducing B6HO3 cells to produce IFN-γ. Based on the present and also previous findings, we propose that IL-18 released from macrophages because of cell death caused by bacteria may be the primary cytokine that triggers the innate IFN-γ production that is required for activating the bactericidal functions of macrophages at early stages of bacterial infection.